A educação popular no PET/conexões de saberes: contribuições para a formação e identidade docente dos egressos - Santos, Tays de Sousa (2021)
This study deals with teacher training, focusing on the construction of teachers’ professional identity, based on the experiences of the Tutorial Education Project (PET) Knowledge Connections: Access and Permanence of Young People of Popular Origin to the University (University - Community Dialogues), which develops actions based on the perspective of Popular Education at the Federal University of Paraíba. The Project participants are of popular origin, linked to an undergraduate course and carry out teaching, research and extension activities at the university level and in the communities from which they come. Some of the Project's initiatives are the pre-university course, study group and teacher training actions for Youth and Adult Education. Thus, the general objective of this study was to analyze the contributions of the PET Project/ Knowledge Connections: Access and Permanence, based on the Popular Education, to the teacher training and construction of the professional identity of its egress graduates. Methodologically, the research has a qualitative character, and some of its guiding references are, among others, authors such as Freire (1967, 1979, 2001, 2002, 2014), Nóvoa (2004, 2019), Farias et al. (2009), Streck et al. (2014), Sales (1999), Melo Neto (2004, 2013), Calaça (2013, 2015, 2016, 2018) and Chizzotti (2000). Some of its analytical categories are as follows: dialogue, autonomy, teaching identity as a procedural resignification and liberating education. The empirical research was carried out with six egress graduates of the PET Project/ Knowledge Connections, through semi-structured interviews, and the data were treated based on the thematic-categorical content analysis technique proposed by Bardin (1977). It was possible to verify that the contributions of the PET Project/Knowledge Connections, based on the Popular Education, for the teacher training and the construction of the professional identities of its egress graduates are materialized in its actions as the study group, and concern to the development of the sense, for example, of social justice, solidarity, collaborative work, participation, dialogue and autonomy.